2012
DOI: 10.3201/eid1808.111053
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniaein Gastrointestinal Tract and Pyogenic Liver Abscess

Abstract: To determine the role of gastrointestinal carriage in Klebsiella pneumoniae liver abscess, we studied 43 patients. Bacterial isolates from liver and fecal samples from 10 patients with this condition and 7 healthy carriers showed identical serotypes and genotypes with the same virulence. This finding indicated that gastrointestinal carriage is a predisposing factor for liver abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 15 publications
5
121
1
2
Order By: Relevance
“…Patients with pyogenic liver abscesses have been reported to have frequent intestinal (81.4%) and/or pharyngeal (39.5%) colonization with hvKP [29]. We found hvKP colonization in 16 patients.…”
Section: Discussionmentioning
confidence: 51%
“…Patients with pyogenic liver abscesses have been reported to have frequent intestinal (81.4%) and/or pharyngeal (39.5%) colonization with hvKP [29]. We found hvKP colonization in 16 patients.…”
Section: Discussionmentioning
confidence: 51%
“…It is unclear what role our patient's prior biliary surgery may have played in the pathogenesis of her disease, though it is conceivable that her altered anatomy may have been a predisposing factor. Gastrointestinal carriage of the K1 strain is likely a risk factor for development of K. pneumoniae liver abscess (24). Diabetes is a frequent underlying illness in reports of K. pneumoniae hepatic abscess (5, 25), but our patient lacked that putative risk factor as well.…”
mentioning
confidence: 77%
“…Although a report has shown that sequence type 14 (ST14) in serotype K2 isolates was not associated with virulence (16), this should not decrease the need to detect serotypes K1 and K2 in patients with clinical illness. Previous studies have shown that K. pneumoniae serotype K1 and/or K2 contamination can be detected in milk from cows with mastitis (8), and intestinal colonization of serotype K1/K2 isolates is a predisposing factor for the development of human disease as well (14,17). Therefore, the ability to specifically detect serotypes K1 and K2 may help to prevent future complications in infected patients (10).…”
Section: Resultsmentioning
confidence: 99%